The Singapore stock options market. - Chan, Seow Wai. (2013)
The Singapore stock options market was launched on 8 March 1993. Its launching is a necessary step towards developing Singapore into an international financial centre. However, the potential of the stock options market has not been fully exploited by investors, evident from the low trading volume to-date. This project attempts to show an overview of the stock options market, determine factors that are critical to its success and identify the strengths and weaknesses of the Singapore stock options market.